2020
DOI: 10.18632/aging.103433
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A2 serves as a potential biomarker and therapeutic target for ovarian cancer

Abstract: The solute carrier (SLC) family is the largest group of membrane transporters, but their functions in ovarian cancer (OV) remain unclear. We analyzed SLC family members with amino acids-transporting functions in OV. The mRNA expression levels and prognostic values of SLCs in OV were analyzed in the Gene Expression Profiling Interactive Analysis and Kaplan–Meier Plotter database. Solute carrier family 7 member 2 (SLC7A2), which showed differential expression and the most significant prognostic value, was select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…At present, studies have found that SLC7A2 plays critical roles in ovarian cancer and breast cancer 38 , 39 . Loss of SLC7A2 augments inflammation-associated colon tumorigenesis 21 .…”
Section: Discussionmentioning
confidence: 96%
“…At present, studies have found that SLC7A2 plays critical roles in ovarian cancer and breast cancer 38 , 39 . Loss of SLC7A2 augments inflammation-associated colon tumorigenesis 21 .…”
Section: Discussionmentioning
confidence: 96%
“…SLC7A2 is a novel biomarker for the diagnosis and treatment of OC. 24 PRDX-1 expression in tumor tissue can be a biomarker for the prognosis of patients with OC. 25 Increased expression of TET3 predicts an unfavorable prognosis for OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the SBT vs. HGSOC comparison, such genes included SLC7A , PIFO , RPL7A , and CRABP2 [ 57 61 ] (Table S 10 ). In fact, SLC7A2 serves as a potential biomarker and therapeutic target for ovarian cancer [ 62 ]. The remaining seven DEGs in the SBT vs. HGSOC comparison, while not previously reported in association with ovarian cancer, have cancer or disease-related functions.…”
Section: Discussionmentioning
confidence: 99%